THE ROLE OF ISLĀMIC DA'WAH IN PROMOTING HIGHER ISLAMIC OBJECTIVES (THE OBJECTIVE OF MONEY AS A MODEL) AN ANALYTICAL STUDY - Abdul Ghias Sohrabi; Dr. Abdul Wahab Jan (Journal of Religion and Society, 2025)
This research addresses the role of Islāmic Da'wah in Promoting Higher Islamic Objectives (Maqasid al-Shari'ah) in general and particularly it addresses the role of Islāmic Da'wah in preserving the Objective of property (Maqsad-al-mal), and that is because it is obvious for everyone that the Islāmic Da'wah is a Da’wah prescribed by Allah Almighty, and endeavor to introduce human to Allah Almighty Divine Laws, as he wants His servants to study these laws, understand them well, and act accordingly. Hence, it contains great benefits (Masalih) that are necessary to prevent human from great harms. It also promote the necessities (Darurat), the supplemental requirements (Hajiyat), and the beautifications or embellishments (Tahsinat) that the preacher must be aware of and prioritize necessities over supplemental requirements, as well as supplemental requirements over beautifications in the case of conflict. This knowledge benefits the preacher (Da’EE) and benefits the Islāmic Da'wah, and shortens efforts and saves time. We have chosen the Objective of property as a model because the Muslim scholars agreed that money is considered one of the necessary purposes of Islamic law, and it is called good (Khair) in many noble verses, as God Almighty says: (And indeed, he is in love of wealth, intense) and He said: (And whatever you spend of good – it will be fully repaid to you, and you will not be wronged). Therefore, the money/property is very crucial for humankind, and Therefore, Islamic Sharia has devoted great care to its preservation and maintenance, and has established methods to ensure the collection of wealth and its protection from loss or abuse. Having said that, given the importance of this topic, as a researcher I decided to write a scholarly article entitled "The Role of Islāmic Da'wah in Promoting Higher Islamic Objectives (The Objective of Money as a Model) An Analytical Study. Keywords: Money/property, Da’wah, and Higher Islamic Objectives (Maqasid al-Shari'ah)